Correlations of Depression Level with Gender and Family Support Among Elderly with Chronic Diseases - Agil Priambodo; Imanuela, Andrea Chalista (Universitas Muhammadiyah Surakarta, 2025)
Chronic disease often causes depression in the elderly, especially for women. Elderly need family support to deal with the depression. This study was aimed to analyze whether there was a correlation between family support, gender, and depression levels in the elderly. Utilizing the DASS-21, the family support assessment, and questions about characteristic of respondent, data was obtained which were then analyzed using the Spearman method, with confidence level was 95%. The Spearman’s analysis yielded a correlation coefficient of -0.026, and a Sig. (2-tailed) of 0.817 between depression and family support. Likewise, the correlation coefficient was 0.070, and Sig. (2-tailed) was 0.537 between depression and gender. It can be concluded that there was a weak correlation between the three variables, but it was not statistically significant. Further study is needed to analyze the influence of confounding factors as a predictor model of depression levels in the elderly.